2019
DOI: 10.21608/ejmm.2019.282890
|View full text |Cite
|
Sign up to set email alerts
|

Study of mcr-1 Gene-Mediated Colistin-Resistance in Gram-Negative Isolates in Egypt

Abstract: Background:The re-use of colistin (last-resort drug) to treat infections caused by resistant Gram-negative bacteria, has led to the emergence of a serious resistance against colistin. A new transferable plasmid-mediated colistin-resistance gene (mcr-1) has been described globally. Screening for such gene will provide an aiding step to explore the extent of colistin-resistance in Egypt. Objectives: To isolate the causative Gram-negative bacteria from different hospital-acquired (HA) and community-acquired (CA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…These data revealed high colistin resistance percentage compared to previous studies that showed complete sensitivity to colistin 10 and another study that demonstrated that only 1 isolate from 66 P. aeruginosa isolates was resistant to colistin. 28 In the present study, the homology analysis (using ERIC-PCR) revealed that plasmidmediated carbapenemases and colistin resistance genes could be easily transmitted across the P. aeruginosa isolates. Most of the tested isolates were unrelated to each other; however, they all included one or more carbapenemase gene.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…These data revealed high colistin resistance percentage compared to previous studies that showed complete sensitivity to colistin 10 and another study that demonstrated that only 1 isolate from 66 P. aeruginosa isolates was resistant to colistin. 28 In the present study, the homology analysis (using ERIC-PCR) revealed that plasmidmediated carbapenemases and colistin resistance genes could be easily transmitted across the P. aeruginosa isolates. Most of the tested isolates were unrelated to each other; however, they all included one or more carbapenemase gene.…”
mentioning
confidence: 55%
“…Screening for the existence of β-lactamases genes involving bla VIM , bla IMP , bla NDM-1 , bla KPC and bla OXA-48 and colistin resistance gene (mcr-1) was established by PCR using the primer sets listed in Table 1. [28][29][30][31][32] The PCR reactions were established in the volume of 25 μL. Each PCR reaction consisted of 3 μL of template DNA, 1 μL forward primer (10 μM), 1 μL of reverse primer (10 μM), 12.5 μL Dream Taq PCR master mix 2x (Fermentas, USA) and 7.5 μL nuclease free water.…”
Section: Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
“…Zafer et al reported 22 (4.9%) colistin-resistant K. pneumoniae isolated over 18 months from cancer patients in Egypt [44] . Colistin resistance was detected in 8 (7.5%) K. pneumoniae in Tanta University Hospitals according to Ezzat et al [45] . Rabie et al found that 17.2% of K. pneumoniae isolates were resistant to colistin at Zagazig University Hospitals [46] .…”
Section: Discussionmentioning
confidence: 99%
“…This is because E. coli isolates that produce MCR -1 have been determined in animal food products [9]. The thoughtless use of colistin in the veterinary sector, particularly in the lack of severe lawmaking has contributed to the global dispersal of the MCR -1 gene in 10% of animal isolates and in 0.1–2% of human isolates [10].…”
Section: Introductionmentioning
confidence: 99%